2019
DOI: 10.1016/j.ejor.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches for zero forcing and related problems

Abstract: In this paper, we propose computational approaches for the zero forcing problem, the connected zero forcing problem, and the problem of forcing a graph within a specified number of timesteps.Our approaches are based on a combination of integer programming models and combinatorial algorithms, and include formulations for zero forcing as a dynamic process, and as a set-covering problem. We explore several solution strategies for these models, test them on various types of graphs, and show that they are competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 60 publications
2
43
0
Order By: Relevance
“…Some of these results, as well as analogous results about a connected variant of zero forcing, have been reported in[10].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Some of these results, as well as analogous results about a connected variant of zero forcing, have been reported in[10].…”
supporting
confidence: 76%
“…A fort of a graph G, as defined in [30], is a non-empty set F ⊂ V such that no vertex outside F is adjacent to exactly one vertex in F . Let F (G) be the set of all forts of G. In [11], it was shown that Z(G) is equal to the optimum of the following integer program:…”
mentioning
confidence: 99%
“…This disparity has been attributed to the non-locality of the connected domination problem, since exact algorithms are often unable to capture global properties like connectivity [29]. In some contrast, computational experiments in [13] have shown that algorithms for connected zero forcing are slightly faster than algorithms for zero forcing. Thus, in this aspect, power domination seems to behave more like domination than like zero forcing.…”
Section: Computational Resultsmentioning
confidence: 99%
“…Requiring a power dominating set to be connected is motivated by the application in monitoring electrical networks: the data from PMUs is relayed by high-speed communication infrastructure to processing stations which collect and manage this data; thus, in addition to minimizing the production costs of the PMUs, an electric power company may seek to place all PMUs in a compact, connected region in the network in order to reduce the number of processing stations and related infrastructure required to collect the data.Connected power domination was explored from a computational perspective in [27] (although the problem called "connected power domination" in [27] is slightly different from the one considered here; see Section 6 for details). The connected variants of other graph problems, including connected zero forcing [13,14,15], connected domination [20,23,29,47], and connected vertex cover [19,36], have also been extensively studied. Imposing connectivity often fundamentally changes the nature of a problem, including its complexity, structural properties, and applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation